The Measurement Comparison between Hadlock and Hadlock 4 Formulas in the Second and Third Trimesters Obstetric Ultrasound for Foetal Weight and Delivery Estimation - Sari, Gando; Sriyatun; Zumarnis, Fellya; Apriantoro, Nursama Heru (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze the results of Hadlock and Hadlock 4 formulation measurement on pregnant women in the second and third semester obstetric ultrasound scan for foetal weight and delivery estimation. The design of this research is quantitative analytic. Data analysis was done by T-Test. This research was conducted from October to November 2019. The population of this research was taken from the entire number of Obgyn ultrasound examinations and 30 research samples. Based on the research, it can be concluded that an analysis of the estimated labor time with the Hadlock and Hadlock 4 obtained the results of *Tbirth-2 with an average labor time of 34.40 days while *Tbirth-4 is 40.87 days. There is a difference in the Sig. (2-tailed) value of 0,000